JUNIOR HIGH SCHOOL STUDENTS’ DIGITAL LITERACY LEVEL DURING LEARNING IN PANDEMIC TIME - Mega Risna Damayanti Peoni; Novalita Fransisca Tungka (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
This research aims to determine the level of digital literacy of junior high school students during learning in pandemic time. The nature of this research is a descriptive quantitative, and data are collected through distributing online questionnaires to 106 respondents from three junior high schools in Mori Atas sub-regency, Morowali regency, Central Sulawesi. The results showed that during pandemic time, the level of digital literacy of junior high school students in Mori Atas sub-regency reaches intermediate level in the aspects of digital information processing, creating digital content, and safety and problem solving in accessing digital information. This implies that the junior high school students in Mori Atas sub-regency are ready for a digital-age learning culture in their near future.